Implementasi Blue Economy dalam Pengelolaan Hasil Laut di Desa Pasir Putih Kabupaten Konawe Kepulauan - Rita Lapantasi Bubun; Murniati Murniati; Muhammad Rizaldi Makmur (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The abundant fishery resources in Pasir Putih Village are not accompanied by appropriate and sustainable fish handling methods. This has resulted in economically valuable catches remaining unsold and being discarded.  The goal of the community-based service activity is to enhance the sustainable use of fishery resources through the implementation of the blue economy. The activity involves stages of socialization, training, technology application, and support and evaluation. The results of The Community Empowerment activity conducted by the Pucuk Kolosua Women’s Group in Pasir Putih Village improved the participants' knowledge and skills by 95% in sustainable fishery resource use through the application of the blue economy concept. To ensure the program’s sustainability, support from the Konawe Kepulauan local government through the Department of Industry, Trade, Cooperatives, and Small and Medium Enterprises is needed to provide supporting equipment, such as shrimp cracker drying facilities. This support will enable continued innovation and creation in the diversification of processed fishery products and the sustainable use of fishery resources based on local wisdom.